Transcriptome sequencing analysis of the role of miR-499-5p and SOX6 in chicken skeletal myofiber specification - Liu, Yi-Fan; Zhang, Ming; Shan, Yan-Ju; Pang, Li-Chuan; Ji, Gai-Ge; Ju, Xiao-Jun; Tu, Yun-Jie; Shi, Shi-Ying; Bai, Hao; Zou, Jian-Min; Shu, Jing-Ting (Frontiers in Genetics, 2022)
MicroRNAs (miRNAs) might play critical roles in skeletal myofiber specification. In a previous study, we found that chicken miR-499-5p is specifically expressed in slow-twitch muscle and that its potential target gene is SOX6. In this study, we performed RNA sequencing to investigate the effects of SOX6 and miR-499-5p on the modulation and regulation of chicken muscle fiber type and its regulatory mechanism. The expression levels of miR-499-5p and SOX6 demonstrated opposing trends in different skeletal muscles and were associated with muscle fiber type composition. Differential expression analysis revealed that miR-499-5p overexpression led to significant changes in the expression of 297 genes in chicken primary myoblasts (CPMs). Myofiber type-related genes, including MYH7B and CSRP3, showed expression patterns similar to those in slow-twitch muscle. According to functional enrichment analysis, differentially expressed genes were mostly associated with muscle development and muscle fiber-related processes. SOX6 was identified as the target gene of miR-499-5p in CPM using target gene mining and luciferase reporter assays. SOX6 knockdown resulted in upregulation of the slow myosin genes and downregulation of fast myosin genes. Furthermore, protein-protein interaction network analysis revealed that MYH7B and RUNX2 may be the direct targets of SOX6. These results indicated that chicken miR-499-5p may promote slow-twitch muscle fiber formation by repressing SOX6 expression. Our study provides a dataset that can be used as a reference for animal meat quality and human muscle disease studies.